An intervention program based on team building during tactical training tasks to improve team functioning - Tassi, Juan M.; López-Gajardo, Miguel A.; Leo, Francisco M.; Díaz-García, Jesús; García-Calvo, Tomás (Frontiers in Psychology, 2023)
The study aimed to analyze the effects of an intervention program based on team building developed in technical-tactical training tasks in football. Specifically, it examined the benefits of the intervention in variables related to the conceptual model of team building: role clarity, team identification, intra-team communication, cohesion, intra-group conflict, commitment to the team, inside sacrifice, transactive memory systems, collective efficacy, and perceived performance. The participants were 51 young elite footballers divided into an experimental group (n = 27) and a control group (n = 24). The methodological design was quasi-experimental with a duration of eight weeks. The data were collected three times: pretest, posttest, and follow-up. The results showed differences favoring the experimental group compared to the control group after the implementation of the intervention program in the following variables: team identification (p < .001), role clarity (p < .001), intra-team communication (p < .001; except distinctiveness), group cohesion (p < .05), social conflict (p = .001), commitment to the team (p < .001), inside sacrifice (p < .001), transactive memory systems ( p < .01; except cooridation), collective efficacy (p = .02) and team performance (p = .001). Consequently, the application of team-building strategies incorporated into specific technical-tactical training tasks in football seems to improve group dynamics in sports teams.